Pengaruh Penggunaan ChatGPT dan Google Scholar dalam Mencari Sumber Informasi Akademik Bagi Mahasiswa - Hadid Pangestu, Arya; Setiyawan, Alan; Syahrul Romadhon, Muhammad; Sutiawan, Hedi; Rizki Pratama, Adrian; Maulana Asviara, Daffa; Satini, Satini; Zulkarnaen, Iskandar (Rifa'Institute, 2024)
This study aims to collect and analyse students' assessment of the use of ChatGPT and Google Scholar in finding academic information sources. Data was collected through a questionnaire designed to evaluate ease of use, quality of information obtained, and impact on students' learning process. The results of the questionnaire were analysed using statistical methods to ensure the validity and reliability of the findings. Normality test, validity test, and reliability test were conducted to ensure data distribution and reliability. The results showed that the Cronbach's Alpha value of 0.8290 confirmed that the data was reliable. The correlation coefficient between 0.600 to 0.800 shows a high correlation, indicating the significant influence of using ChatGPT and Google Scholar in helping students find and understand academic information. Nonetheless, some limitations need to be noted, such as limitations in interpretation and analysis that require in-depth understanding as well as customisation to specific academic contexts.